Bandgap Engineering in InAs/GaSb II Superlattices: Modulation and Vacancy Defects Analysis - Yan Jiang; Yulin Zhou; Zongyao Zhang; Zhengdao Li; Liyuan Jiang; Xinxin Zhao; Jianbao Wu (Photonics)
The computational analysis of InAs/GaSb type-II superlattices utilizing density functional theory (DFT) with pseudopotentials has been performed. The PBE+U method was employed to correct for the strong correlation effects of the P orbitals of In, As, Ga, and Sb, thereby improving the accuracy of the bandgap calculations. The study investigated the impact of the number of layers in the InAs and GaSb bulk materials on the superlattice bandgap. The results revealed that as the number of InAs layers increased while keeping the number of GaSb layers constant, the bandgap decreased. Conversely, when the number of GaSb layers increased with a constant number of InAs layers, the bandgap increased. In conjunction with the interface issues and vacancy defects frequently encountered in InAs/GaSb type-II superlattices, electronic structure analyses indicate that InAs, as the primary electron aggregator, significantly influences the modulation of the superlattice bandgap.